THE (IN) EXISTENCE OF A CRISIS OF REPRESENTATIVENESS IN BRAZIL (Revista Paradigma, 2022)
This article aims to investigate if there is a representative crisis in the Brazilian democratic scenario, caused by the absence of dialogue and identification of voters with their representatives. It will initially discuss the nuances of representative government in a democracy, and then ask whether the political representation in Brazil focuses on the figure of the candidate or the political party. Causing direct impact on representative democracy, therefore, results in a mismatch and disbelief in politics, possibly leading to a crisis of representativeness. For this, the research methodology will be analytical and will be based on the combination of investigative proposals, such as bibliographic research. The paper will have as theoretical framework Bernand Manin and Nadia Urbinati, who seek to investigate and identify the possible cleavages of representation and its consequences in a representative democracy. The reason that justifies this article is to discuss whether the contemporary democratic scenario of Brazil, in what refers to democracy and representative government are in line with the social reality or presents itself in crisis. As a result, it can be verified that the Brazilian electoral behavior is still not stable, and it is not possible to verify if there is a crisis of representativeness, although there are indications in the current political scenario.